Quasi-static and dynamic magnetic tension forces in arched, line-tied magnetic flux ropes. (22nd November 2016) - Myers, C E; Yamada, M; Ji, H; Yoo, J; Jara-Almonte, J; Fox, W
Abstract: Solar eruptions are often driven by magnetohydrodynamic instabilities such as the torus and kink instabilities that act on line-tied magnetic flux ropes. Recent laboratory experiments designed to study these eruptive instabilities have demonstrated the key role of both dynamic (Myers et al 2015 Nature 528 526) and quasi-static (Myers et al 2016 Phys. Plasmas 23 112102) magnetic tension forces in contributing to the equilibrium and stability of line-tied magnetic flux ropes. In this paper, we synthesize these laboratory results and explore the relationship between the dynamic and quasi-static tension forces. While the quasi-static tension force is found to contribute to the flux rope equilibrium in a number of regimes, the dynamic tension force is substantial mostly in the so-called failed torus regime where magnetic self-organization events prevent the flux rope from erupting.